Pyrroloquinoline quinone prevents developmental programming of microbial dysbiosis and macrophage polarization to attenuate liver fibrosis in offspring of obese mice. Issue 3 (22nd January 2018) - Friedman, Jacob E.; Dobrinskikh, Evgenia; Alfonso‐Garcia, Alba; Fast, Alexander; Janssen, Rachel C.; Soderborg, Taylor K.; Anderson, Aimee L.; Reisz, Julie A.; D'Alessandro, Angelo; Frank, Daniel N.; Robertson, Charles E.; de la Houssaye, Becky A.; et al.
Abstract : Exposure to maternal Western‐style diet induces early gut symbiosis, polarization of bone marrow‐derived macrophages, and induction of hepatic inflammation in the offspring that persists into adulthood. These programs are attenuated by short‐term maternal treatment with the dietary anti‐oxidant, pyrroloquinoline quinone. Abstract : Increasingly, evidence suggests that exposure to maternal obesity creates an inflammatory environment in utero, exerting long‐lasting postnatal signatures on the juvenile innate immune system and microbiome that may predispose offspring to development of fatty liver disease. We found that exposure to a maternal Western‐style diet (WD) accelerated fibrogenesis in the liver of offspring and was associated with early recruitment of proinflammatory macrophages at 8‐12 weeks and microbial dysbiosis as early as 3 weeks of age. We further demonstrated that bone marrow‐derived macrophages (BMDMs) were polarized toward an inflammatory state at 8 weeks of age and that a potent antioxidant, pyrroloquinoline quinone (PQQ), reversed BMDM metabolic reprogramming from glycolytic toward oxidative metabolism by restoring trichloroacetic acid cycle function at isocitrate dehydrogenase. This resulted in reduced inflammation and inhibited collagen fibril formation in the liver at 20 weeks of age, even when PQQ was withdrawn at 3 weeks of age. Beginning at 3 weeks of age, WD‐fed mice developed a decreased abundance of Parabacteroides and Lactobacillus, together with increased Ruminococcus and decreased tight junction gene expression by 20 weeks, whereas microbiota of mice exposed to PQQ retained compositional stability with age, which was associated with improved liver health. Conclusion : Exposure to a maternal WD induces early gut dysbiosis and disrupts intestinal tight junctions, resulting in BMDM polarization and induction of proinflammatory and profibrotic programs in the offspring that persist into adulthood. Disrupted macrophage and microbiota function can be attenuated by short‐term maternal treatment with PQQ prior to weaning, suggesting that reshaping the early gut microbiota in combination with reprogramming macrophages during early weaning may alleviate the sustained proinflammatory environment, preventing the rapid progression of nonalcoholic fatty liver disease to nonalcoholic steatohepatitis in offspring of obese mothers. ( Hepatology Communications 2018;2:313‐328)